The Development of Interactive Multimedia Based on Technological Pedagogical Content Knowledge (TPACK) to Improve the Learning Outcomes of 5th Grade Elementary School Students - Winda Boyusta; Rayendra; Abna Hidayati; Ridwan (Postgraduate, University of Mataram, 2025)
This study aims to develop interactive multimedia based on Technological Pedagogical Content Knowledge (TPACK) to improve fifth-grade elementary students’ learning outcomes. The research was motivated by students’ low learning interest, limited use of engaging learning media, and insufficient tools to support material comprehension. This research used a Research and Development (R&D) approach with the 4D model, consisting of the stages of Define, Design, Develop, and Disseminate (limited to the development stage). The multimedia’s validity was evaluated by material, media, and language experts; practicality was measured through teacher and student response questionnaires; and effectiveness was analyzed using pretest–posttest data with a t-test. The findings indicate that the developed multimedia met the validity, practicality, and effectiveness criteria, showing improvements in students’ learning outcomes. The developed TPACK-based multimedia proved suitable for use in Pancasila Education for grade V elementary school. The study implies that the multimedia can enhance student engagement, promote independent learning, and strengthen understanding of Pancasila values within Indonesia’s cultural diversity. However, the study was limited to the development phase and has not yet undergone large-scale dissemination.